PENGUASAAN VERBA BENTUK-TE UNTUK MENYATAKAN KEGIATAN SEDANG BERLANGSUNG DAN KEGIATAN BERURUTAN PADA PESERTA DIDIK KELAS XI IPA SMA PGRI 6 DENPASAR TAHUN AJARAN 2016/2017 - Dewa Gede Agung Aditya K; I Nyoman Suparwa; Made Sri Satyawati (Universitas Warmadewa, 2018)
[Title: Mastering verb form of –te for declaring ongoing and sequential activity on the students of grade XI IPA SMA PGRI 6 Denpasar Academic Year 2016/2017] This research is aimed to know (1) the ability in mastering verb form of -te on the students of grade XI IPA SMA PGRI 6 Denpasar. (2) The difficulty is faced by the students of grade XI IPA SMA PGRI 6 Denpasar in the use of verb form of –te. The research with this qualitative descriptive design has research subject, that is the students of grade XI IPA SMA PGRI 6 Denpasar and research object, that is verb form of -te. The data is collected through test method. The data is analysed with qualitative and quantitative. The result of the research shows that (1) the ability in mastering the verb form of -te on the students of grade XI IPA SMA PGRI 6 Denpasar belong to lack category, average mark achieved is 50. There are six students 24 % students get enough mark and 19 students 76 % students achieved mark lack;(2) the dificulty is faced by the sudents of grade XI IPA SMA PGRI 6 Denpasar in the use of verb form of -te stated the running activity and ordering activity based on the test result that is the students still confused with the use of verb form of -te between doublé consonant /t/ and /t/ which is not doublé such as mi-ru verb in the verb form of -te become mi-te not mi-tte because mi-ru verb belong to ichidandoushi which is replace gobi(ru) become /te/ and attach with basic morferm verb (mi) so become mi-te.